농촌지역 사회자본의 존재 양태 분석 - 정기환 (한국농촌경제연구원, 2003)
A Study on the Forms of Social Capital in Rural Community It is a general evaluation that Korea has achieved a significant development in the agricultural sector in a relatively short period. There has been argues what has brought such development in the Korean farm sector. Often, technology development and capital formation are considered as the main force of development. However, if it is true, why Korean rural areas has been deteriorated since the 1980s even though there is a significant development of technology and capital formation in the farm sector? This study aims to identify the relationship between rural development and social capital formation. This study hypothesizes that social capital has a keen relationship with rural community development. Therefore deteriorating rural areas in Korea since 1980s might have a negative relationship to the social capital formation. This study will be continued for three years, and this report, as the first research, focused on conceptualizing social capital and identifying the forms of social capital in rural communities. Conventionally, social capital has been conceptualized as "the norms and social relations embedded in the social structure of society that enable people to coordinate action and to achieve desired goals." Some studies identify social capital to the social groups and volunteer associations. However, this concept is vague and obscure to grasp the meaning od social capital. Therefore, this study re-conceptualized social capital, which is measurable and verifiable in the Korean rural context. This study defined social capital as "an ability enforcing people in social group or social network to take action for achieving desired goals", and this ability should be made through social interactions of social exchange, compensation, cooperation, competition, and conflict. The case study implemented in 4 rural villages identified that the above social interactions are related to social capital. A rural community is composed of social groups. The community, an administrative unit, is a kind of social group itself. Interest groups in economic and social sphere are commonly organized. Consanguineous groups overlap the community and interest groups. During 1986?2002, social groups in the 4 rural villages diminished by 46.1 percent. The community and consanguineous groups standing as before without significant changes. However, most remarkably, economic interest groups diminished by 91.1 percent. Instead, social interest groups reduced by 45.5 percent during the period. This means that economic activities in rural communities have been radically reduced and therefore, social capital embedded in social groups in rural communities also diminished. Social exchange and compensation, and cooperation among members of social groups are very common behaviors producing social capital. Most social groups have means of social compensation for the membership. The members of social groups in the case study have information channels from outside, means of access to common properties such as agricultural land, forestry and common fund for lending. Most social groups have cooperation mechanism for obtaining the goal. There are two most common forms of cooperation: labor and cash contribution. There is a strong penalty when members violate the norms and regulations. The more social exchange and compensation exist, the higher degree of cooperation is found. Competition based on fair rules could be a source of social capital as it brings better results among members. Competition was found until the 1970s. However, it is very rare in the case villages. Conflict could also be a source of social capital since it produce better alternatives through negotiations. Conflict were observed in the irrigation kye and cooperative farming. The members of cooperative farming groups could overcome conflicts among members and could find better way of cooperative marketing and quality control. Social capital reduced when government intervenes indigenous social groups. Traditional village community and irrigation kye become less autonomous as government intervene increases. Since 1977, when different social groups were integrated into one under the prime minister's decree, social groups have been powerless and members lost their identity. Therefore, government policy should not intervene existing social groups and social capital when it is introduced to rural community. Researcher: Chung, Ki-Whan E-mail address: kwchung@krei.re.kr
Keywords: 농촌지역; 사회자본; 지역발전